Função normativa do executivo e seus limites: a legística aplicada ao Direito Ambiental - Frederico José Gervasio Aburachid (2012)
The boundaries of the regulatory function exercised by the Executive is a matter of great controversy, especially when discussing the development and implementation of the Environmental Law. Besides the formal laws, the Environmental Law includes more than fifteen (15) types of acts, such as decrees, resolutions, Normative Resolutions, Ordinances, Instructions, etc.. These normative acts are edited to regulate the use of property, economic activities and exploitation of natural resources etc. It is a fact. Public Administration is increasingly present in the integration of normative systems, publishing general and abstract acts previously reserved only for formal law. Despite this fact, the traditional administrative law (present in most manuals of academic programs in Law) retains the theoretical concepts based on strict principle of legality and tripartition of State Power. In this sense, there are interpreters, among them lawyers, Judges, Prosecutors and University Professors who still support the idea that the Executive cannot innovate in rights and obligations. The research deals with a very current issue, what is the definition of the limits of this regulatory function performed by the Executive, especially in the brazilian subsystem of the Environmental Law. Finally, the Legistics, field of knowledge that studies the quality of law, is adopted as a way to get the rationality in the elaborative process of environmental normative acts, within a reinterpretation of the principle of legality to the support of its conclusions.